TIPS FOR ACHIEVING SUCCESS ACCORDING TO THE BOOK (MIFTAH AL-NAJAH BY AID AL-QARNI) - Firdaus, Aisyah; Budianti, Yusnaili; Alfarabi, Mohammad (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2025)
This study uses a qualitative research method with a character study approach that is included in the category of library research. A descriptive-analytical approach is used to describe the steps to achieve success, as well as the characteristics of successful people according to Aid al-Qarni's views. The results of the study show Aid al-Qarni's career journey and thoughts in the fields of education, preaching, and Islamic literacy. Aid al-Qarni has made great contributions through his works that have inspired many people. Furthermore, discussing the steps to achieve success as explained in Miftah al-Najah which emphasizes sincerity, discipline, and wise use of time as the keys to success. In addition, the characteristics of successful people according to Aid al-Qarni include strong faith, hard work, and concern for others. Through a combination of spiritual and moral values, individuals can achieve true success that is not only worldly, but also brings blessings. Therefore, educational institutions are advised to integrate Islamic success values ​​into the curriculum, workers and business actors apply Islamic ethics, and society instills a culture of hard work and social concern.